Political and legal significance of the Charter of fundamental rights of the European Union (Journal of actual problems of jurisprudence, 2023)
The legal space of the European Union as a whole refers to the extent to which the legal norms of this organization are spread. The political and legal significance of the Charter of Fundamental Rights of the Union in its legal space follows from the legal force and the implementation of the provisions of this document. Therefore, the role of the Charter of Fundamental Rights of the European Union in the field of regulation and supervision of the activities of structures operating on its basis is determined by the new political and legal significance of the Charter (having legal binding force) in the EU legal space. However, despite the fact that over time fundamental research was carried out in this area, and as a result of the analysis of literature and scientific articles on the participation of Kazakhstan in international cooperation with the states of the European Union to protect human rights and fundamental freedoms, it became known that this topic insufficiently studied in domestic legal science.These are, of course, important factors that determine the relevance of this topic. The main purpose of the article is to prove the place and significance of the Charter of Fundamental Rights of the European Union in the system of protection of human rights and fundamental freedoms. The article highlights some current political and legal issues related to the Charter of Fundamental Rights of the European Union, its implementation and prospects. Also, the article considers the real and possible aspects of the issue of obtaining the relevant international legal obligations by the Republic of Kazakhstan as a partner of the European Union under the aforementioned Charter. The conclusions presented in the article can be used in the practical implementation of the Charter of Fundamental Rights of the European Union. It can also be taken into account when fulfilling the international obligations of the Republic of Kazakhstan.Keywords: Charter, agreement, international organization, member states, partner states, European law.